Think like a monk train your mind for peace and purpose every day - Shetty, Jay (Thorsons, 2020)
Jay Shetty, social media superstar and host of the #1 podcast 'On Purpose', distils the timeless wisdom he learned as a practising monk into practical steps anyone can take every day to live a less anxious, more meaningful life. In this inspiring, empowering book, Shetty draws on his time as a monk in the Vedic tradition to show us how we can clear the roadblocks to our potential and power. Drawing on ancient wisdom and his own rich experiences in the ashram, Think Like a Monk reveals how to overcome negative thoughts and habits, and access the calm and purpose that lie within all of us. The lessons monks learn are profound but often abstract. Shetty transforms them into advice and exercises we can all apply to reduce stress, improve focus, improve relationships, identify our hidden abilities, increase self-discipline and give the gifts we find in ourselves to the world. Shetty proves that everyone can - and should - think like a monk.